Peningkatan Kesadaran Bahaya Hoax Dan Hate Speech Pada Remaja Masjid Dan Sekaa Truna Truni Bali Utara - Sari Dewi Noviyanti (IAHN Gde Pudja Mataram, 2022)
North Bali itself is one of the areas in Bali with a high Muslim population. Nowadays, it is not uncommon for friction between groups to occur on social media, especially when it is triggered by the behaviours of individuals who often spread hate speech and hoax. The purpose of this activity is to provide assistance to the younger generation of North Bali as part of this nation's generation to prevent them from spreading hoax and hate speech, especially on social media. The method used in this community service activity is seminars and workshops with the number of participants in the activity being 20 representatives of mosque youth and Sekaa Truna Truni. From the results of the community service activities, there was an increase in the understanding of the youth representatives of the mosque and the truna truni in understanding social media ethics, especially in dealing with hate speech content and fake news.